Hyponatremia after neuroendoscopic skull base tumor surgery: Clinical characteristics and nursing management - Yang, Yanjun; Lv, Chunmei; Zhang, Jing; Zhao, Yuanli (Frontiers in Surgery, 2022)
OBJECTIVE The study aimed to retrospectively summarize the nursing experience of 181 patients with hyponatremia after neuroendoscopic resection of a cranial base tumor in our hospital from 2016 to 2021. METHODS The key points of nursing for patients with hyponatremia after neuroendoscopic cranial base tumor resection are as follows: 1) timely and accurate nursing evaluation; 2) close observation of patients’ the clinical manifestations; 3) timely and accurate specimen collection and timely inspection; 4) proper and reasonable use of sodium supplements according to the classification of hyponatremia; 5) focus on shift succession; 6) health education in response to changes in the patient’s condition. RESULTS 44 patients with postoperative hyponatremia were corrected in 3-11 days after the implementation of the above nursing measures, and no serious neurological damage such as demyelination occurred. CONCLUSION Care for patients with hyponatremia after resection of a skull base tumor under neuroendoscopy requires nurses to possess clinical professional knowledge, standardize and accurately implement various nursing measures, and fully communicate and cooperate with doctors to promote patients' recovery.